Solar Power Battery Management System - Nitin Gaikwad, Soojey Deshpande, Sneha Salvekar, Swati Joshi (Mathematical Statistician and Engineering Applications, 2022)
This essay describes an easy solar-powered battery monitoring system that employs numerous batteries as input from the sun. The state of a single battery is only minimally monitored by the suggested method. The battery voltage & power flows, which are the two parameters currently monitored, may be used to determine the depth of discharge (DOD), state of charging (SOC), and state of health (SOH) of the battery, among other features. using a straightforward design method that interfaces an Atmega 328 with readily accessible and reliable voltage and current sensors to read data. This system also shows the readings’ outputs and maps the various features on a simple-to-use Graphical User Interface (GUI) built on the C platform. The suggested system includes a mechanism for power cut-off to prevent battery overcharging. Real-time data access from the battery being carried out, and all output parameters, even minute variations brought on by changing solar circumstances, are presented.